2010
DOI: 10.1016/j.brainres.2009.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral six-hydroxydopamine administration to PFC prevents the expression of behavioral sensitization to methylphenidate

Abstract: Psychostimulants like amphetamine and methylphenidate (MPD) are used to treat attention deficit hyperactivity disorder (ADHD), which is marked by developmentally inappropriate inattention, hyperactivity, and impulsivity. Neuropsychological analyses indicate that ADHD patients are impaired on tasks of behavioral inhibition, reward reversal, and working memory, which are functions of the prefrontal cortex (PFC) and are modulated by the mesocortical dopamine (DA) system. Non-specific electrical lesioning of PFC e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 81 publications
3
31
2
Order By: Relevance
“…The NAc mediates reward behavior through dense dopaminergic projections from the ventral tegmental area (VTA) [6]. The VTA interacts with the pre-frontal cortex (PFC) glutamatergic transmission facilitating the rewarding actions of psychostimulants [7,8]. The NAc also receives excitatory glutamatergic inputs from the thalamus, hippocampus, and amygdala [9].…”
Section: Introductionmentioning
confidence: 99%
“…The NAc mediates reward behavior through dense dopaminergic projections from the ventral tegmental area (VTA) [6]. The VTA interacts with the pre-frontal cortex (PFC) glutamatergic transmission facilitating the rewarding actions of psychostimulants [7,8]. The NAc also receives excitatory glutamatergic inputs from the thalamus, hippocampus, and amygdala [9].…”
Section: Introductionmentioning
confidence: 99%
“…Both DA and GABA neurons in the VTA get input mediated by GABA and glutamate; those afferents containing glutamate come from the PFC, while those of GABA originate in the NAc (Beckstead et al, 1979; Johnson and North, 1992; Kalivas and Duffy, 1995). The dopaminergic neurons in the VTA co-express GABA-ergic or glutamatergic markers and it is thought that these DA neurons are activated by the glutamatergic inputs originating in the PFC and are involved with the induction of behavioral sensitization following repetitive exposure of psychostimulants (Scheggi et al, 2002; Tang et al, 2009; Wanchoo et al, 2010). In a morphological study, it has been shown that about two-thirds of the neurons in the VTA are dopaminergic, while the remaining neurons are mostly GABA (Nair-Roberts et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This may give rise to striatum dysfunction, leading to hyperactivity and learning deficits. Consistent with this possibility, MPH loses its locomotor-stimulating effects when selective dopaminergic lesions are made using 6-hydroxydopamine in the striatum [42] but not in the PFC [43]. A combined double lesion in the nucleus accumbens and striatum resulted in a severe deficit in the conditioned avoidance responding test [44].…”
Section: Discussionmentioning
confidence: 99%